KETIMPANGAN RELASI KETATANEGARAAN DALAM PEMBENTUKAN UNDANG-UNDANG ANTARA DPR, DPD DAN KABINET PASCA AMANDEMEN UUD NRI TAHUN 1945 - Helen, Zennis; Siregar, Sahnan Sahuri (Fakultas Hukum Universitas Nahdlatul Wathan Mataram, 2019)
Relationship of the state administration in the formation of laws between the DPR and DPD and how they relate to the cabinet of Joko Widodo-Jusuf Kalla. The risk of constitutionality that will be posed due to the unequal relations in the constitutional formation of the law. The solution to overcome this inequality. The constitutional relationship between the DPR and the DPD is really lame. This can be seen from the authority of the two institutions in the 1945 Constitution of the Republic of Indonesia. The DPR has the power to form laws. Whereas the DPD in particular in the formation of laws only has very little legislative rights when compared to the DPR. The lack of authority of the DPD poses a risk to the institution so that the DPD whose members are both elected by the people in the election and the budget from the state is not optimal in carrying out its functions, especially in the formation of laws. Until now, none of the bills that were born from the DPD initiative and the imbalance in the state administration relationship must be ended by changing the fifth 1945 Constitution, and for the short term President Joko Widodo-Ma, Ruf Amin must reactivate the Regional Autonomy Ministry in the next cabinet as a coordinating path for the DPD in defending regional interests.